2008
DOI: 10.1007/s00221-008-1643-y
|View full text |Cite
|
Sign up to set email alerts
|

Gait capacity affects cortical activation patterns related to speed control in the elderly

Abstract: Functional decline in locomotion is common among the elderly, and the prevalence of gait disorders increases with age. Recently, increasing interest has been focused on the influence of age-related decline in brain function and neurological disorders such as dementia and Alzheimer's disease on gait capacity. However, the neural mechanisms underlying gait control in the elderly remain poorly understood. We examined whether cortical activation patterns associated with the control of gait speed were related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
237
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(251 citation statements)
references
References 74 publications
14
237
0
Order By: Relevance
“…However, power increases in the left/right sensorimotor cortices were more pronounced for contralateral limb push-off than for ipsilateral limb push-off. Studies carried out with fNIRS also showed involvement of frontal, premotor, and supplementary motor areas during walking (Harada et al 2009;Miyai et al 2001;Suzuki et al 2004Suzuki et al , 2008. These results support the idea that walking is represented across a plurality of cortical brain areas.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…However, power increases in the left/right sensorimotor cortices were more pronounced for contralateral limb push-off than for ipsilateral limb push-off. Studies carried out with fNIRS also showed involvement of frontal, premotor, and supplementary motor areas during walking (Harada et al 2009;Miyai et al 2001;Suzuki et al 2004Suzuki et al , 2008. These results support the idea that walking is represented across a plurality of cortical brain areas.…”
Section: Discussionsupporting
confidence: 67%
“…Neuroimaging studies show that rhythmic foot or leg movements recruit primary motor cortex (Christensen et al 2001;Dobkin et al 2004;Heuninckx et al 2005Heuninckx et al , 2008Luft et al 2002;Sahyoun et al 2004), whereas electrophysiological investigations demonstrate electrocortical potentials related to lower limb movements (Wieser et al 2010), as well as a greater involvement of human cortex during steady-speed locomotion than previously thought (Gwin et al , 2011. In this regard, studies using functional near-infrared spectroscopy (fNIRS) show involvement of frontal, premotor, and supplementary motor areas during walking (Harada et al 2009;Miyai et al 2001;Suzuki et al 2004Suzuki et al , 2008. That primary sensorimotor cortices carry information about bipedal locomotion has been directly proven by the work of Nicolelis and colleagues (Fitzsimmons et al 2009), who demonstrated that chronic recordings from ensembles of cortical neurons in primary motor (M1) and primary somatosensory (S1) cortices can be used to predict the kinematics of bipedal walking in rhesus macaques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both SPECT studies, task execution (walking) was carried out prior to image acquisition. Using near-infrared spectroscopy (NIRS), Miyai et al (2001) studied gait on a treadmill and found gait-related activity in S1, M1 and SMA, thus corroborating earlier findings of Fukuyama et al To our knowledge, NIRS is the only technique to date that has been applied to carry out gait performance and image acquisition simultaneously (Miyai et al 2001;Suzuki et al 2004Suzuki et al , 2008Harada et al 2009). Unfortunately, there are well-known limitations of this technique, and in the study of Miyai et al (2001), spatial distribution and intensity of the gait-induced metabolic changes were not statistically evaluated.…”
Section: Introductionsupporting
confidence: 79%
“…stimulus evoked HHb decreases in only a few channels), whilst that of HbO 2 is more generalised with typical responses being observed in almost all NIR channels (Cannestra et al, 2003;Hirth et al, 1997;Sato et al, 2007). Additionally, studies demonstrate that decreases in HHb do not have a uniform tendency across all subjects Miyai et al, 2001), with investigators being unable to detect statistically Miyai et al, 2001Miyai et al, , 2002Miyai et al, ‡, 2003Suzuki et al, 2004Harada et al, 2009Miyai et al, 2001Miyai et al, , 2002Miyai et al, ‡, 2003Harada et al, 2009Mihara et al, 2007 ‡;Miyai et al, 2001Miyai et al, , 2002Miyai et al, ‡, 2003Suzuki et al, 2004Harada et al, 2009Mihara et al, 2007 ‡;Miyai et al, 2001Miyai et al, , 2002Miyai et al, ‡, 2003Suzuki et al, 2004Harada et al, 2009Mihara et al, 2007 ‡;Miyai et al, 2001Miyai et al, , 2002Miyai et al, , 2003Suzuki et al, 2004Harada et al, 2009Miyai et al, 2002Miyai et al, ‡, 2003 Study design: case series unless indicated as follows: longitudinal cohort/repeated measures study (*), randomised comparison/cross-over ( †), non-randomised comparison (...…”
Section: Temporal Dynamics Of the Observed Cortical Haemodynamic Respmentioning
confidence: 91%